2011
DOI: 10.1074/jbc.m111.301234
|View full text |Cite
|
Sign up to set email alerts
|

The Multi-zinc Finger Protein ZNF217 Contacts DNA through a Two-finger Domain

Abstract: Background: Classical C2H2 zinc finger proteins generally bind DNA via a three-finger motif. Results: We have identified the DNA site recognized by ZNF217 and defined its mechanism of binding. Conclusion: Two classical C2H2 zinc fingers, rather than the typical three, are sufficient to bind an eight base pair sequence. Significance: This work broadens our understanding of DNA binding by classical zinc fingers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 63 publications
(41 reference statements)
6
26
0
Order By: Relevance
“…4). As shown previously (34), substantial chemical shift changes are observed following the addition of WT DNA, and these changes are consistent overall with the structure of the complex. Fig.…”
Section: Znf217 Recognizes Its Cognate Dna Sequence Using a Unique Insupporting
confidence: 66%
See 3 more Smart Citations
“…4). As shown previously (34), substantial chemical shift changes are observed following the addition of WT DNA, and these changes are consistent overall with the structure of the complex. Fig.…”
Section: Znf217 Recognizes Its Cognate Dna Sequence Using a Unique Insupporting
confidence: 66%
“…Our measurements indicated that a GST fusion of ZNF217_F67 recognizes the WT DNA sequence with a relatively low affinity (K d ϭ 130 nM). Even more surprisingly, the affinity was reduced by only 2.5-fold when the core recognition sequence was extensively mutated (from TGCAGAAT to CTGGAGTA) (34). A similar affinity was observed for binding to a poly(AT) sequence (supplemental Fig.…”
Section: Znf217 Recognizes Its Cognate Dna Sequence Using a Unique Insupporting
confidence: 51%
See 2 more Smart Citations
“…Fluorescence polarization measurements were carried out as previously described (Nunez et al, 2011, Rossi & Taylor, 2011 at 25°C on a PHERAstar© FS microplate reader (BMG). The 6-carboxyfluorescein (FAM)-labelled dsDNA probes (2nM) were incubated for 20 min with increasing amounts of protein in 50mM Tris-HCl (pH8.0), 150mM NaCl, 200mM Glutathione-reduced, 50μM ZnCl2, 5mM TCEP, 10% NP-40.…”
Section: Fluorescent Polarisationmentioning
confidence: 99%